MONITORING THE URBAN HEAT ISLAND EFFECT IN BAGHDAD USING SENTINEL-3 AND OSM DATA INTEGRATION FOR SUSTAINABLE URBAN PLANNING - Alshammari , Lubna Alshammari; Ridha, Suaad; Al-shammari , Mustafa (Journal of Applied Engineering Science, 2025)
The rapid expansion of urban areas has accelerated the urban heat island (UHI) phenomenon, exacerbated by climate change’s effects. Therefore, the long-term sustainability of the urban regions faces a severe challenge. The study investigates the magnitude of the UHI phenomenon in Baghdad using Land Surface Temperature (LST) data acquired from the Sentinel-3 satellite and OpenStreetMap (OSM) urban infrastructure data. This study examines the changes in the UHI between 2016 and 2023. It tends to determine the spatial distribution of UHI concerning different cities and investigate the relationship between the effects of urban development and the magnitude of UHI. In this regard, the data indicated that the magnitude of UHI increased significantly during the measured period. The mean temperature rise has reached 1.34°C throughout the city, with a particularly significant increase of 2.6°C in the highly populated regions inside the municipality boundaries. An empirical investigation reveals a strong positive correlation between building density (0.89) and road density (0.823) with the intensity of the UHI. Conversely, the green areas display a moderate negative correlation (-0.56) linked to the UHI intensity. The results illustrate the substantial impact of urban infrastructure development on the UHI, defined by remarkably high UHI coefficients in heavily populated areas. Thus, the study results will provide valuable policy suggestions that will significantly help the relevant policymakers and urban planners in their efforts to enhance urban resilience and public health in Baghdad. It is also a systematic and organized approach that can be applied in other rapidly urbanizing areas.